Use of suburban landscapes by the Pileated Woodpecker (Dryocopus pileatus). (22nd August 2018) - Tomasevic, Jorge A.; Marzluff, John M.
Abstract: Urban areas continue to expand, with cities now containing more than half of the world's population. As cities grow, natural habitat is transformed, changing the face of the local biota and the resources available for it. Wherever woodpeckers are present, the cavities that they excavate provide an important ecological service that facilitates many other species. We studied how the Pileated Woodpecker ( Dryocopus pileatus ) uses suburban areas. From 2009 to 2013, we used radio-telemetry to determine the annual home range size and habitat use of 13 individuals in 9 suburbs that varied in their level of urbanization (ranging from 5% to 90% forest remaining). We used concentration of use and resource utilization functions to examine vegetative characteristics used by woodpeckers at relatively large (i.e. 1 km 2 ) and more local (i.e. ⅓ ha) scales. The average home range of suburban Pileated Woodpeckers was significantly smaller than expected based on previous studies. Pileated Woodpeckers concentrated their use of the landscape in native coniferous and deciduous forest, as well as in lightly and moderately urbanized areas. Highly urbanized areas were seldom used. For males, resource use increased with increasing mean diameter of dominant hardwood species. Our results suggest that maintaining forest cover above 20% and retaining large deciduous trees and snags in public green spaces and yards may improve the suitability of suburban areas for woodpeckers and the biodiversity that they facilitate.